THE HESITATION BETWEEN AL-I’RAB AND AL-BINAA IN ARABIC WORDS - Mohammed Ridha, Aiad; Dhaya Eddine, Benferdia (International Journal of Psychosocial Rehabilitation, 2022)
The reader of grammar books notes that Mo’rab and Mabni words are either contained in separate chapters, such as the chapters on verbs, pronouns, nouns, relative nouns, relative nouns, Categorical negative lâ and its noun and predicate, vocative noun, and other chapters, or they are grouped in a separate chapter, As it is in: “Al-Alfiyya of Ibn Malik” in the chapter of al- Mo’rab and al- Mabni, “Sharḥ sudhụr al-Dhahab” by Ibn Hisham al-Ansari, the chapter of Al-I’rab, the chapter of al-Binaa, “Ham' al-Hawami'” by al-Suyuti, the chapter of Al-I’rab and its place, and alBinaa and its place, and other works.What appears from this distinction is that it is nothing more than a formality, because words, whether nouns, verbs or letters, are either Mo’rab or Mabni, and talking about them and their grammatical issues is a must in grammar books, either based on their being mo’rab or mabni or not, Whoever started from the fact that the words are either Mo’rab or Mabni has classified it in this classification and touched on each Mo’rab and its issues until he finished, and then to each Mabni and its issues until he was finished, and so on, and who did not start from that classification dealt with each Mo’rab and each Mabni in its chapter allocated to him, and then talked about his issues and related matters, including Al-I’rab and Al-Binaa.However, there are words that are sometimes in their origin mo’rab words, and are exposed to AlBinaa, and other times in their origin are mabni words and exposed to Al-I’rab, to form a phenomenon that deserves attention to it, and stand on it. This research that we are presenting is an attempt to highlight this linguistic phenomenon, and its title: " The hesitation between Al-I’rab and Al-Binaa in Arabic words", and the problem that we have sought to solve in this is our question about the extent of the impact of this phenomenon on Arabic speech, and the extent to which it contributes to highlighting the flexibility and diversity of eloquent Arabic vocabulary, and does this phenomenon deserve to be a third independent section in addition to the Mo’rab words and mabni words sections? This research aims to praise the characteristics of our eloquent Arabic language and to call for further reflection and scrutiny of its vocabulary and structures to reveal the extent of its diversity.